2016
DOI: 10.1080/09593330.2016.1198424
|View full text |Cite
|
Sign up to set email alerts
|

Culture scale-up and immobilisation of a mixed methanotrophic consortium for methane remediation in pilot-scale bio-filters

Abstract: Robust methanotrophic consortia for methane (CH) remediation and by-product development are presently not readily available for industrial use. In this study, a mixed methanotrophic consortium (MMC), sequentially enriched from a marine sediment, was assessed for CH removal efficiency and potential biomass-generated by-product development. Suitable packing material for bio-filters to support MMC biofilm establishment and growth was also evaluated. The enriched MMC removed ∼7-13% CH under a very high gas flow ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Likewise, it was recently indicated that CO2 contributed to better SCP yield on CH4 (Khoshnevisan et al, 2019). Similarly, CO2 encouraged the growth of the mixed methanotrophic consortium in pilot-scale biofilters (Karthikeyan et al, 2017). Both type I (gammaproteobacteria) and type II (alphaproteobacteria) methanotrophs have PEP-carboxylase for CO2 assimilation 11 (Karthikeyan et al, 2015).…”
Section: Resultsmentioning
confidence: 94%
“…Likewise, it was recently indicated that CO2 contributed to better SCP yield on CH4 (Khoshnevisan et al, 2019). Similarly, CO2 encouraged the growth of the mixed methanotrophic consortium in pilot-scale biofilters (Karthikeyan et al, 2017). Both type I (gammaproteobacteria) and type II (alphaproteobacteria) methanotrophs have PEP-carboxylase for CO2 assimilation 11 (Karthikeyan et al, 2015).…”
Section: Resultsmentioning
confidence: 94%
“…Apart from the improving effect of MOB immobilization, the high porosity and ample pore volume of support materials might be another improving factor. The gas could enter into these pores, which might prolong the gas retention time in biofilters and enhance the contact chance between MOB cells and methane, and consequently further promoted methane elimination (Karthikeyan et al, 2017;Wu et al, 2017). Similarly, in existing studies, the active carbon prepared from biogas digestate has been used as support material to immobilize MOB consortium in a biofilter to dispose 0.9% (v/v) of methane, and reached a methane EC of 2.08 g h −1 m −3 , which was almost four folds of that of the suspended MOB cells (Wu et al, 2017); A ladscale methane biofilter regarding tobermolite as support material was installed to mitigate 5% (v/v) of methane, and the methane ECs ranged from 27.72 g h −1 m −3 to 28.96 g h −1 m −3 were obtained (Kim et al, 2014a) (Table 3).…”
Section: Methane Elimination and Mob Immobilization Performancesmentioning
confidence: 99%
“…Methane-oxidizing bacteria consortia have been inoculated in biofilters packed with various support materials, such as active carbon, perlite, stones, and polypropylene spheres, to mitigate methane emissions (Kim et al, 2014b;Karthikeyan et al, 2017;Wu et al, 2017). Compared to the suspended MOB cells, the immobilized MOB cells on support materials performed better in methane elimination because of the higher biomass concentration, more excellent metabolic activity and superior tolerance to severe environmental conditions (Cohen, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed herein that reductions in CH4 concentrations are the result of biotic oxidation processes. We did not perform microbiological tests that would confirm the presence of -or an increase in -active methanotrophic consortia, such as documented by Gebert et al (2003), Humer and Lechner (1999) and Karthikeyan et al (2017Karthikeyan et al ( , 2016.…”
Section: Acclimatization Processmentioning
confidence: 99%